In situ hollow nanoarchitectonics of MIL-88A@Co(OH)2 composites for supercapacitors and oxygen evolution reactions. (3rd February 2023) - Jiang, Shuyao; Li, Shuke; Liu, Zhejun; Xu, Yanchao; Zhang, Yubin; Zhang, Ling; Xu, Yanqiu; Li, Shasha; Jiao, Yang; Chen, Jianrong
Abstract : The Co(OH)2 conductive channel strategy was designed to improve the electrochemical performance of MiL-88A. Abstract : Efforts have been made to pursue multifunctional electrode materials, and their practical applications have been promoted for energy storage and conversion equipment. Currently, constructing composite materials is considered a promising strategy. Reasonable structural design is important to improve the conductivity of MOF materials. In this study, a simple hydrothermal method is employed to develop ultrathin Co(OH)2 nanosheets on an iron-based metal–organic framework (Fe-FA, MIL-88A) to create Fe-FA@Co(OH)2 composites with hollow and interconnected porous network structure. A large specific surface area with hierarchical porous structure is provided for electrolyte storage, which promotes the diffusion of ions and significantly improves the reaction kinetics of the active material. Furthermore, the hollow structure can expose more active surfaces, resulting in improved mass diffusion efficiency. The synergistic effect of Fe-FA and Co(OH)2 endows the composites with better energy storage and electrocatalytic performance than pristine Fe-FA. The specific capacity of Fe-FA@Co(OH)2 is 275 mA h g −1 at 1 A g −1 . The Fe-FA@Co(OH)2 //AC asymmetric supercapacitor benefits from the aforesaid advantages, and its energy and power densities are 73.1 W h kg −1 and 800 W kg −1, respectively. For the oxygen evolution reaction, Fe-FA@Co(OH)2 provides an overpotential of 275 mV at 10 mA cm −2, which demonstrates a well-designed electrode material with excellent performance and is an inspiration for future energy storage and conversion devices.